2020
DOI: 10.3889/oamjms.2020.5388
|View full text |Cite
|
Sign up to set email alerts
|

MASKNE: Mask-Induced Acne Flare During Coronavirus Disease-19. What is it and How to Manage it?

Abstract: The coronavirus disease (COVID)-19 is a global pandemic caused by severe acute respiratory syndrome (SARS)-CoV-2. Due to the rapid spread of the disease, several measures have been proposed to mitigate its transmission, including wearing a mask in certain circumstances. This new proposition leads to some novel skin adverse effects; one of them is acne flare. This particular outbreak has significantly affected people’s quality of life. In this minireview, a brief current knowledge of SARS-CoV-2 and its related-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 32 publications
0
26
0
6
Order By: Relevance
“…Given the significantly positive correlation between cosmetics and acne (Perera et al, 2018 ), the sealing effect of the mask makes the wearer more susceptible to acne flare-ups. It is popularly known as “maskne or mask acne” (Kosasih, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the significantly positive correlation between cosmetics and acne (Perera et al, 2018 ), the sealing effect of the mask makes the wearer more susceptible to acne flare-ups. It is popularly known as “maskne or mask acne” (Kosasih, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…9 According to one study, 59.6% of people who wear masks on a regular basis have acne breakouts. 10 Owing to prolonged use of facemasks, maskne is well-recognized in healthcare workers as compared to the general population. 11 A study showed that about two dozen healthcare professionals were diagnosed with acne over a period of less than 3 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Several other authors have also reported mask-induced flaring of acne, suggesting a new nomenclature —'mask acne. '[ 13 ] Indoor restriction and less photo-exposure due to lockdowns and a replenished ozone layer due to reduced pollution during this pandemic have been proposed to be a possible factor for reduced incidence of malignant melanoma, however, there are concerns that, in fact, the incidence rate has not dropped, and instead, we have missed cases and skin cancer clinics need to continue as normal. [ 14 ] Dermatophytosis, a condition which had already acquired an epidemic-like scenario prior to the COVID-19 pandemic, is being increasingly encountered, with a distinct presentation on the facial area covered by masks.…”
Section: Discussionmentioning
confidence: 99%